2013
DOI: 10.3727/096368912x655064
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Population Isolated from the Subepithelial Layer of Umbilical Cord Tissue

Abstract: The therapeutic use of stem cells to treat diseases and injuries is a promising tool in regenerative medicine. The umbilical cord provides a rich source of stem cells; we have previously reported a population of stem cells isolated from Wharton's jelly. In this report, we aimed to isolate a novel cell population that was different than those found in Wharton's jelly. We isolated stem cells from the subepithelial layer of the umbilical cord; the cells could be expanded for greater than 90 population doubling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…Although bone marrow is the main source, MSCs have already been isolated from various other tissues, such as adipose tissue (22) and umbilical cord (23). Choudhery et al (24) reported that confluent cultures of MSCs either from adipose tissue or cord tissue show a fibroblastic morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Although bone marrow is the main source, MSCs have already been isolated from various other tissues, such as adipose tissue (22) and umbilical cord (23). Choudhery et al (24) reported that confluent cultures of MSCs either from adipose tissue or cord tissue show a fibroblastic morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have since reported the establishment of MSC-like cells from a variety of fetal (29) and adult mesenchymal tissues, including nonhematopoietic tissues (31,32,34,36). The potential of MSC-like cells isolated from nonhematopoietic tissues to support HSCs still remains unclear, while the HSC-supporting potential of BM-MSCs is well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Hematopoietic stem cells (HSCs) can self-renew and differentiate into all types of blood cells (2,14,29). These HSCs are maintained in an undifferentiated state in a specialized environment, which is called the HSC niche (17,19).…”
Section: Introductionmentioning
confidence: 99%
“…Banked human umbilical cord mesenchymal stem cells (hUC‐MSCs; Jadi Cell LLC, Miami, USA; Patel, Vargas, Revello, & Bull, 2013) were cultured in cell culture media with Dulbecco's Modified Eagle's Medium (DMEM; Life Technologies, USA) supplemented with either 10% hPL (Jadi Cell LLC) or 10% FBS (Life Technologies), 1% Glutamax (Life Technologies), 1% MEM NEAA (Life Technologies), 1% penicillin streptomycin (Life Technologies), at 37°C in a humidified atmosphere with 5% CO 2 from passage 2 (P2) to P12. Cell culture media was changed every 2 days.…”
Section: Methodsmentioning
confidence: 99%